PERBANDINGAN MINAT SISWA-SISWI SMA FAVORIT DI KOTA DAN SMA FAVORIT DI DESA TERHADAP EKSTRAKURIKULER BOLAVOLI (STUDI PADA SISWA-SISWI SMA NEGERI 1 BOJONEGORO DAN SMA NEGERI 1 SUMBERREJO) - IRAWAN, ERIK (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Interest basically, is the acceptance of some relation between its own self with something outside self. The bigger or closer a relation, so the interest will be stronger. Extracurricular is a student activity that done outside school hour that have function to develop talent, interest and also stimulate physic growth and student character and also improving student concerning matters that taught in extracurricular. One of the curricular that exist on SMA Negeri 1 Bojonegoro and SMA Negeri 1 Sumberrejo is volleyball. Problem formulation that proposed in this research is how is the student of SMA Negeri 1 Bojonegoro interest to volleyball extracurricular? How is the student of SMA Negeri 1 Sumberrejo to volleyball extracurricular? The type of research that applied is descriptive qualitative (non experiment) that aime to reveal information as much as possible from respondent without give treatment. Design that applied is comparative designs (comparison) that compare one group to other group. Population in this research is SMA Negeri 1 Bojonegoro and SMA Negeri 1 Sumberrejo to volleyball extracurricular. From the research result obtained that the interest of SMA Negeri 1 Bojonegoro to extracurricular as big as 67,91% while the student of and SMA Negeri 1 Sumberrejo is 68,52% that categorized moderate. While on t test, t count is 0,103 that not bigger than t table 1,990, thus, it stated that there is no difference between the interest of urban favorite high school student and village favorite high school student to volleyball extracurricular especially on students of SMA Negeri 1 Bojonegoro and SMA Negeri 1 Sumberrejo. Keywords: Interest, Volleyball Extracurricular